Environmental Physics Learning: Implementation and Assessment in Higher Education - Henukh, Anderias; Diana Rochintaniawati, Diana; Riandi, Riandi; Setiawan, Agus; Irvani, Asep Irvan; Aini, Rahmi Qurota (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This analysis of environmental physics learning is significant because it examines the efficacy of innovative pedagogical approaches in physics with a focus on environmental applications. This study summarizes the comprehensive evaluation and reconstruction of the environmental physics program, which aims to align it with contemporary society's demands and urgent environmental management needs. This study aims to describe the planning, implementation, assessment, and student response to learning or lecturing environmental physics. The instruments used in this study were observation sheets for planning, implementation, and assessment, as well as a questionnaire of student responses to environmental physics lectures. The data analysis results show that the average percentage of environmental physics learning planning falls into the sufficient category at 65%. The average implementation of learning or environmental physics lectures is 78% good. The assessment score for learning environmental physics was 61.67%, placing it in the sufficient category. The student response to the implementation of environmental physics lectures was mixed, with 21.1% stating it was not interesting and 78.9% stating it was quite interesting.